CONCENTRATION AS A FACTOR IN THE FORMATION OF ECONOMIC EFFICIENCY OF MILK PRODUCTION IN AGRICULTURAL ENTERPRISES (International Journal of Innovative Technologies in Economy, 2020)
The purpose of the research is to assess the impact of the level of production concentration in dairy farming on its efficiency. The study was conducted on the example of agricultural enterprises of Kharkiv and Chernihiv regions of Ukraine. Theoretical provisions concerning the influence of production concentration on various aspects of efficiency were generalized in the article. It is emphasized that this process is objective and takes place in different countries. The advantages of large milk production enterprises are in greater opportunities for the use of technical means and savings at the level of fixed costs.The study has found that there is a clear relationship between the grouping criterion and the value of profitability, productivity of cows, based on the analysis of factual data on the results of agricultural enterprises grouping as to the volumes of milk sale. This dependence is direct. In addition, the relationship between the grouping indicator and the growth of milk production per 100 hectares of agricultural land, production intensity is quite clearly stated. In Kharkiv region, these dependencies are clearer. The scientific value of the research results lies in their practical orientation, considering the established dependencies when planning both the level of concentration, and milk production intensity in agricultural enterprises.